2013
DOI: 10.1515/ijb-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis for Causal Inference under Unmeasured Confounding and Measurement Error Problems

Abstract: In this article, we present a sensitivity analysis for drawing inferences about parameters that are not estimable from observed data without additional assumptions. We present the methodology using two different examples: a causal parameter that is not identifiable due to violations of the randomization assumption, and a parameter that is not estimable in the nonparametric model due to measurement error. Existing methods for tackling these problems assume a parametric model for the type of violation to the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…An estimator's robustness can be evaluated by performing hypothesis tests across levels of a sensitivity parameter, which represents an overall degree of violation from statistical assumptions (e.g., unmeasured confounding, misclassification, and lack of overlap between exposed and unexposed patient characteristics). This approach can be applied either parametrically or non-parametrically across a broad range of study designs and effect parameters [16,17]. For matching analyses, a similar approach is to establish Rosenbaum bounds that assess the strength of confounding required to undermine the conclusions about causal effects [18].…”
Section: Alternative Assessment Of Uncertaintymentioning
confidence: 99%
“…An estimator's robustness can be evaluated by performing hypothesis tests across levels of a sensitivity parameter, which represents an overall degree of violation from statistical assumptions (e.g., unmeasured confounding, misclassification, and lack of overlap between exposed and unexposed patient characteristics). This approach can be applied either parametrically or non-parametrically across a broad range of study designs and effect parameters [16,17]. For matching analyses, a similar approach is to establish Rosenbaum bounds that assess the strength of confounding required to undermine the conclusions about causal effects [18].…”
Section: Alternative Assessment Of Uncertaintymentioning
confidence: 99%
“…As a next step in the roadmap, we develop targeted estimators of the statistical estimand and develop the theory for statistical inference. To understand the deviation between the estimand and the causal quantity under a variety of violations of these causal assumptions, one may carry out a sensitivity type analysis [1618, 36], which represents the final step of the roadmap.…”
Section: Introductionmentioning
confidence: 99%
“…However, the simulation also demonstrated that unmeasured confounding can have an impact on estimation, which makes developing relevant sensitivity analyses (e.g., Rotnitzky et al, 2001;Díaz and van der Laan, 2013) an important next step.…”
Section: Discussionmentioning
confidence: 99%